Aktivitas Drug Trafficking sebagai Isu Keamanan yang Mengancam Stabilitas Negara - Lumban Tobing, Fredy Buhama (UI Scholars Hub, 2002)
This research is aimed mainly to overlook the phenomenon of drug-trafficking as one of the non-conventional security issues. It also tries to present how this issue is seen through various aspects, with the case study of Southeast Asia in general; and Indonesia in particular. The purpose of this research is to describe the problem through perspective of the threat to state as both the producer and consumer (of the drugs). This perspective is further elaborated through a number of assessments, namely political, military, economic, and social. To explain how this issue develops, the research will be conducted through library research, using supporting and relevant literature. Hopefully, the results of the research are able to give better understanding that the phenomenon of drug-trafficking is mare than just social and health issue. Thus, as the consequence, the policies regarding the issue, whether conducted by the state or through regional mechanisms, have to take more serious forms